ICESat‐2 Pointing Calibration and Geolocation Performance. Issue 3 (11th March 2021) - Luthcke, S. B.; Thomas, T. C.; Pennington, T. A.; Rebold, T. W.; Nicholas, J. B.; Rowlands, D. D.; Gardner, A. S.; Bae, S.
Abstract: ICESat‐2 science requirements are dependent on the accurate real‐time pointing control (i.e., geolocation control) and postprocessed geolocation knowledge of the laser altimeter surface returns. Prelaunch pointing alignment errors and postlaunch pointing alignment variation result in large geolocation errors that must be calibrated on orbit. In addition, the changing sun‐orbit geometry causes thermal‐mechanical forced laser frame alignment variations at the orbit period and trends from days, weeks, and months. Early mission analysis computed precise postlaunch laser beam alignment calibration. The alignment calibration was uploaded to the spacecraft and enabled the pointing control performance to achieve 4.4 ± 6.0 m, a significant improvement over the 45 m (1 σ) mission requirement. Laser frame alignment calibrations are used to reduce the alignment bias and time variation, as well as the orbital variation contributions to geolocation knowledge error from 6 to 1.7 m (1 σ). Relative beam alignment of the six beams is calibrated and shown to contribute between 0.5 ± 0.1 m and 2.4 ± 0.2 m of remaining geolocation knowledge error. Independent geolocation assessment based on comparison to high‐resolution digital elevation models agrees well with the calibration geolocation error estimates. The analysis demonstrates the ICESat‐2 mission is performing far better than its geolocation knowledge requirement of 6.5 m (1 σ) after the laser frame alignment bias variation and orbital variation calibrations have been applied. Remaining geolocation error is beam dependent and ranges from 2.5 m for beam 6 to 4.4 m for beam 2 (mean + 1 σ). Key Points: Systematic time varying pointing errors are the largest ICESat‐2 pointing control and geolocation knowledge error source The systematic pointing errors have been calibrated and corrected to meet and exceed the mission geolocation requirements Further geolocation improvements can be made through the application of the relative beam alignment calibration